Persepsi Karir dan Stigma Sosial Pekerja Perempuan Muda Operator SPBU di Demak-Kudus - Wijaya, Herri; Milad Nufal Akbar; Fifi Endah Irawati; Nur Hayati; Darsin (JOURNAL INTELEKTUAL, 2025)
Introduction/Objective: This study examines the phenomenon of young female workers at public gas stations (SPBU), a sector fraught with gender demands and social stigma. Background Problems: This research explores how female operators in the Demak and Kudus Regencies perceive their careers and navigate this stigma. Novelty: The novelty lies in its focus on the workers' internal perceptions and active resilience. Research Methods: Using a qualitative phenomenological approach, this study collected data through in-depth interviews with 14 informants. Finding/Results: Findings indicate this job is predominantly viewed as a transitional phase, driven by diverse motivations from economic necessity to psychosocial needs for independence. Informants actively navigate stigma, reframing the work as a means to develop non-technical skills like mental fortitude and financial discipline. Conclusion: The study concludes that these workers view this challenging job not as a permanent career, but as a vital developmental stage that provides essential skills for their future aspirations in other careers, entrepreneurship, or domestic life